Senegal's non-compliance with LGBTQ rights claims - Falcão, Ricardo (Activisms in Africa, 2017)
When African States like Senegal ratify international human rights treaties and supposedly new instruments of protections for vulnerable groups become available, the steps taken in the sense of increasing individual rights are seen as socially progressive. The rate of ratification of such instruments has been high in the country, to such an extent that certain people state that Senegal is a country of human rights. Gender rights and sexual and reproductive rights have been widely promoted both at the governmental level and at the grass-roots level, but not those of LGBTQ people. The rights of LGBTQ contrast absolutely with this scenario and violence upon people belonging in this category is very common. Public humiliation, social commentary made by local personalities and high profile religious leaders, and at times even forthright violence like lynching, are outcomes of a very stressed relation of Senegalese society with non-normative sexual identities, especially homosexuality. The country, seen as a “good student” in human rights is at the bottom of the scale of respect for the rights of LGBTQ people. Despite the pressure from the international community for the country pass new laws, it has stood ground, choosing as the interlocutors of the political debate religious groups of pressure and society at large. This ‘non-compliance’ stance can be explained by looking further into the sociocultural context under appreciation. This communication will explore the general framework of gender and intergenerational relations, as well as provide examples, that will help to give meaning to why LGBTQ movements in Senegal haven’t been able to come through.